The Nature of the Virtuous Soul in Al-Ghazali and Hamka - Muhammad Setiawan (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2019)
This paper elaborates the view of al-Ghazali and Hamka on the healthy soul in tasawwuf. Both have an interest correlation in understanding the healthy soul with different way of explanation. Hamka said that the healthy soul should be maintained by four qualities; shajÉ’ah, ‘iffah, Íikmah, and ‘adÉlah. In fact, these four qualities are known as ummahÉt al-fadhÉil or the mother of virtuous in the book of al-Ghazali. In fact, the way of al-Ghazali in explaining the meaning of ummahÉt al-fadhÉil is different with Hamka, so this issue is important to be discussed. This research is done by using the descriptive analysis method to elaborate both views on healthy soul, then comparative method is used to gain the different’s result of thought on this issue. After analyzing this works, researcher finds that Hamka was much influenced by al-Ghazali’s thought, but attractively he was succeeded to contextualize the meaning of healthy soul into Indonesian context. This produces the new explanation which is simple to be understood by all people, especially in the land of archipelago